Vignettes of Buddhist asceticism: jottings on six fragments in Tocharian B - Chen, Ruixuan (Central Asiatic journal, 2018)
This paper consists of a disquisition on six fragments of an otherwise unknown text in Tocharian B, which centers on the Buddhist purification practices known as Skt. dhutaguṇa or Pāli dhutaṅga. Adopting a contextualist approach to the fragmentary text, which is translated and annotated in its entirety for the first time, this study draws on numerous textual sources and ethnographic records with reference to kindred ideas and praxis in various strands of Buddhism and, it is hoped, sheds new light not only on the content and structure of this text per se but also on the religio-historical context in which it was transmitted, and its function and purpose in that milieu.